What to expect from high throughput genomics in metastatic breast cancers?. (1st November 2015) - Onesti, Concetta Elisa; Vicier, Cécile; André, Fabrice
Abstract: Breast cancer is a heterogeneous disease and its genomic characteristics have been widely studied in the last years. Although several progresses have been made, metastatic disease is still incurable in the majority of patients. Recent genomic studies have shown that a large number of candidate targets exist in breast cancer. Currently only two drivers have been validated (ER and HER2), but several others seem to be associated with objective response, such as PIK3CA mutations, FGFR1 amplifications, AKT1 mutations, EGFR amplifications and ERBB2 mutations. Beside driver identification, many other applications can be developed for genomics such as identification of lethal subclones, DNA repair defects or immune response against tumor. Most of the precision medicine programs currently use targeted sequencing. Nevertheless, whole exome sequencing, RNA sequencing, gene expression analysis, phosphoprotein detection, SNP arrays and ctDNA sequencing have been also proposed in clinical trials.